Preparation of a gold@europium-based coordination polymer nanocomposite with excellent photothermal properties and its potential for four-mode imaging. (11th August 2022) - Xia, Faming; Gao, Xuejiao; Shen, Xiaomei; Xu, Hualan; Zhong, Shengliang
Abstract : A nanocomposite was synthesized by replacing the toxic CTAB on the surface of GNRs with a europium-based hyaluronic acid coordination polymer. The nanocomposite exhibits excellent photothermal performance and also has potential for four-mode imaging. Abstract : Gold nanorods (GNRs) with a strong localized surface plasmon resonance (LSPR) effect in the second near-infrared (NIR-II) window are considered as a broad platform for biomedical applications due to their excellent photothermal conversion efficiency, good biocompatibility and tunable surface functionalization. However, bare gold nanoparticles are not stable enough to obtain sufficient energy to kill tumor cells during irradiation. To improve this situation, this study used a europium-based hyaluronic acid coordination polymer (EuCP) to replace the CTAB on the surface of GNRs to prepare a nanocomposite (GNRs@EuCP) with both good biocompatibility and high photothermal conversion efficiency. Under short time radiation with a near-infrared 980 nm laser, the GNRs@EuCP nanorods exhibited good photothermal conversion capability, which is two times higher than that of bare GNRs, with a photothermal conversion efficiency of 74.6%, and exhibited excellent photostability. In addition, this study demonstrates that GNRs@EuCP has the potential for down-convert fluorescence, photoacoustic, CT and photothermal four-mode imaging. This work demonstrates that this gold-based nanocomposite will have great potential for multimodal imaging-guided photothermal therapy.